Neonatal thyrotropin levels and auditory neural maturation in full-term newborns. - Leticia Valerio Pallone (Public Library of Science (PLoS), 2021)
Objective This study aimed to look for a possible relationship between thyrotropin (TSH) values from neonatal bloodspot screening testing and newborn lower auditory pathway myelinization evaluated using the brainstem evoked response audiometry (ABR) test. Methods Sixty-two healthy full-term newborns without perinatal problems were enrolled in the study. TSH results were collected from neonatal bloodspot screening data and were below the test cut-off level (15μUI/mL). The TSH test was performed between three and seven days, and the ABR test was performed in the first 28 days of life. The newborns were divided into two groups: Group 1 (n = 35), TSH between 0 and 5μUI/mL, and group 2 (n = 27), TSH between 5 and 15μUI/mL. Data are presented as mean ± SD, median, or percentage, depending on the variable. Results Wave latency and interpeak interval values for Groups 1 and 2 were as follows: Wave I: 1.8 ± 0.1 and 1.7 ± 0.1; Wave III: 4.4 ± 0.1 and 4.4 ± 0.1; Wave V: 6.9 ± 0.1 and 6.9 ± 0.1; interval I-III: 2.6 ± 0.1 and 2.6 ± 0.1; interval I-V: 5.1 ± 0.1 and 5.1 ± 0.1; interval III-V: 2.4 ± 0.1 and 2.4 ± 0.1. There were no significant differences in ABR parameters between groups 1 and 2 (p > 0.05). Multiple regression analysis showed a slight significant negative correlation between TSH and wave I values (standardized β = -0.267; p = 0.036), without observing any relationship with the other ABR waves recorded. Conclusions This study investigated the relationship of TSH and auditory myelinization evaluated by ABR. It did not show a significant change in lower auditory pathway myelinization according to TSH levels in newborns with TSH screening levels lower than 15 μUI/mL.